N-acetyl-L-cysteine reduces testis ROS in obese fathers but fails in protecting offspring from acquisition of epigenetic traits at cyp19a1 and IGF11/H19 ICR loci - Pastore, Arianna; Badolati, Nadia; Manfrevola, Francesco; Sagliocchi, Serena; Laurenzi, Valentina; Musto, Giorgia; Porreca, Veronica; Murolo, Melania; Chioccarelli, Teresa; Ciampaglia, Roberto; Vellecco, Valentina; Bucci, Mariarosaria; et al. (Frontiers in Cell and Developmental Biology, 2024)
Introduction. Paternal nutrition before conception has a marked impact on offspring's risk of developing metabolic disorders during adulthood. Research on human cohorts and animal models has shown that paternal obesity alters sperm epigenetics, leading to adverse health outcomes in the offspring. So far, the mechanistic events that translate paternal nutrition into sperm epigenetic changes remain unclear. High-fat diet (HFD)-driven paternal obesity increases gonadic ROS, which modulate enzymes involved in epigenetic modifications of DNA during spermatogenesis. Thus, the gonadic pool of ROS might be responsible for transducing paternal health status to the zygote through germ cells. Methods. The involvement of ROS in paternal intergenerational transmission was assessed by modulating the gonadic ROS content in male mice. Testicular oxidative stress induced by HFD was counterbalanced by N-acetylcysteine (NAC), an antioxidant precursor of GSH. The sires were divided into 4 feeding groups: i) control diet; ii) HFD; iii) control diet in the presence of NAC; and iv) HFD in the presence of NAC. After 8 weeks, males were mated with females that were fed a control diet. NAC treatment was evaluated in terms of preventing the HFD-induced transmission of dysmetabolic traits from obese fathers to their offspring. The offspring were weaned onto a regular control diet until week 16 and then underwent metabolic evaluation. The methylation status of the genomic region IGFII/H19 and cyp19a1 in the offspring gDNA was assessed using Sanger sequencing. Results. Supplementation with NAC protected sires from HFD-induced weight gain, hyperinsulinemia, and glucose intolerance. NAC reduced oxidative stress in the gonads of obese fathers and improved sperm viability. However, NAC did not prevent the transmission of epigenetic modifications from father to offspring. Male offspring of HFD-fed fathers, regardless of NAC treatment, exhibited hyperinsulinemia, glucose intolerance, and hypoandrogenism. Additionally, they showed altered methylation at the epigenetically controlled loci IGFII/H19 and cy19a1. Conclusions. Although NAC supplementation improved the health status and sperm quality of HFD-fed male mice, it did not prevent the epigenetic transmission of metabolic disorders to their offspring. Different NAC dosages and antioxidants other than NAC might represent alternatives to stop the intergenerational transmission of paternal dysmetabolic traits.